Nano ceramic coating, preparation method and application thereof

By using nanoceramic coatings with alumina as the base material in protective coatings, combined with flame spraying, water spraying and heat treatment technology, the problems of high porosity and poor corrosion resistance of the coating are solved, and the low porosity of the coating is achieved and high corrosion resistance, extend the service life of the equipment.

CN119463549AInactive Publication Date: 2025-02-18HEFEI KEDE SURFACE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510047349.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the environment where corrosive flue gas is exposed for a long time, existing protective coatings are prone to high porosity and poor corrosion resistance, which leads to a reduction in the bonding force between the coating and the substrate, which leads to the coating falling off.

Method used

Nanoceramic coatings based on alumina are used to form a coating by flame spraying, and water is sprayed and left to stand after curing at room temperature, and then heat treatment is carried out to control the porosity is less than 1%.

Benefits of technology

It achieves the low porosity and high corrosion resistance of the coating, extending the service life of equipment such as boiler water-cooled walls and flues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a nano ceramic coating which is composed of a metal oxide with aluminum oxide as a base material, silicon dioxide and palygorskite, the addition amount of the palygorskite is 11.5-17.3 wt%, and the weight ratio of the silicon dioxide to the palygorskite is (1.1-1.3): 1; the preparation method comprises the following steps: forming a coating from mixed powder of the metal oxide, the silicon dioxide and the palygorskite by a flame spraying method, spraying water, standing, and carrying out heat treatment to form the coating with the porosity of less than 1%. When the nano ceramic coating is applied, the nano ceramic coating is sprayed on the surface of a to-be-protected base material to form a coating with the porosity lower than 1%, and external corrosive components are prevented from making contact with the base material through pores.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of protective coatings, and in particular relates to a nano ceramic coating, a preparation method and application thereof. Background Art

[0002] Nano-ceramic coating is a new type of functional coating material that combines the advantages of nanotechnology and ceramic materials. It uses nano-scale particles as fillers or active ingredients to give the coating a series of excellent properties.

[0003] Ceramic powders such as alumina and zirconia can be used to make high-temperature resistant and corrosion-resistant protective coatings. Due to differences in construction technology and coating components, the final coatings will have different performance.

[0004] In some special application scenarios, the corrosion resistance of the coating will be more concerned. For example, some boiler equipment, supporting water cooling equipment, smoke exhaust pipe equipment, dust removal equipment, etc. will be exposed to corrosive flue gas for a long time. The corrosive substances carried in the flue gas will penetrate into the surface of the substrate through the pores of the coating and corrode the substrate. Over time, the bonding strength between the coating and the substrate will be reduced, which will lead to the shedding of the coating.

[0005] Therefore, studying how to reduce the porosity of the coating is also an important research topic. Summary of the invention

[0006] In view of the above technical problems, this application proposes a nano ceramic coating, a preparation method and its application. The specific technical solutions are as follows: In a first aspect of the present application, a nano ceramic coating is provided, which is composed of a metal oxide based on aluminum oxide, silicon dioxide and palygorskite, wherein the addition amount of the palygorskite is 11.5-17.3wt%, and the weight ratio of the silicon dioxide to the palygorskite is (1.1-1.3): 1; The mixed powder of the metal oxide, silicon dioxide and palygorskite is flame-sprayed to form a coating, and then sprayed with water, left to stand and heat-treated to form a coating with a porosity of less than 1%.

[0007] Preferably, the metal oxide further includes one or more of chromium oxide, iron oxide, zirconium dioxide, tantalum oxide, beryllium oxide, and titanium oxide.

[0008] Preferably, the amount of aluminum oxide added to the total components is not less than 50 wt %.

[0009] Preferably, the size of the silicon dioxide is 5-100 nm, and the D50 particle size is 20 nm.

[0010] Preferably, the coating is formed by flame spraying and then cured at room temperature for 1 to 2 hours.

[0011] Preferably, the standing time after water spraying is 20 to 30 minutes.

[0012] Preferably, when the coating is heat treated, the temperature is 80-150° C. and the time is not less than 24 hours.

[0013] In a second aspect of the present application, a method for preparing a nano ceramic coating is provided, wherein the preparation method comprises: Mix any of the above-mentioned coating powders evenly; The coating is sprayed on the surface of the substrate by flame spraying and cured at room temperature for 1~2h; Press 3~5L / m onto the coating surface 2 After spraying with water, let it stand for 20-30 minutes; The coating is heat treated at a temperature of 80~150℃ for not less than 24h.

[0014] In a third aspect of the present application, an application of a nano-ceramic coating is provided, wherein any of the above-mentioned coatings is sprayed on the surface of a substrate to be protected to form a coating with a porosity of less than 1%, thereby blocking external corrosive components from contacting the substrate through the pores.

[0015] More specifically, the nano-ceramic coating of the present application is applied to the surface of boiler water-cooled walls, boiler flues, etc. to form a protective coating, which can effectively protect the boiler water-cooled walls and boiler flue bodies from being corroded by corrosive substances and extend the service life of the equipment.

[0016] The beneficial effects of the present invention are as follows: the present application uses alumina as a metal oxide base material, and is combined with a small amount of added silicon dioxide and an even smaller amount of added palygorskite as components of a nano-ceramic coating. After forming a coating by flame spraying, a coating with a porosity of less than 1% can be formed after water spraying, standing, and heat treatment. DETAILED DESCRIPTION

[0017] In the following description, certain specific details are set forth in order to provide a thorough understanding of various embodiments. However, it will be appreciated by those skilled in the art that the present invention may be practiced without these details. In other cases, well-known structures are not shown or described in detail to avoid unnecessarily obscuring the description of the embodiments. Unless the context otherwise requires, throughout the specification and the appended claims, the word "comprising" shall be interpreted in an open, inclusive sense, i.e., as "including but not limited to".

[0018] "One embodiment" or "an embodiment" mentioned throughout this specification means that in at least one embodiment, specific features, structures or characteristics related to the embodiment are included. Therefore, the phrases "in one embodiment" or "in an embodiment" appearing in various places throughout this specification do not necessarily all refer to the same embodiment. In addition, specific features, structures or characteristics can be combined in any suitable manner in one or more embodiments. In addition, as used in this specification and the appended claims, the singular forms "one / kind" and "the" include plural referents unless the context clearly dictates otherwise. It should also be noted that the term "or" is generally used in its meaning that includes "and / or" unless the context clearly dictates otherwise.

[0019] The nano ceramic coating of the present application is a coating product based on oxides, wherein the main component of the oxide is aluminum oxide. Aluminum oxide has good performance in high temperature resistance, wear resistance, hardness, chemical stability, etc., and therefore becomes an ideal protective coating material in industry. Of course, it is not excluded that other oxides may also be included in the nano ceramic coating to change or optimize the performance of the coating.

[0020] In the implementation scheme, alumina is used as a metal oxide base material, and a small amount of silicon dioxide and an even smaller amount of palygorskite are added as components of the nano-ceramic coating. The inventors found that when the amount of palygorskite added in the total components is 11.5-17.3wt%, the resulting coating has excellent performance in porosity, especially when the amount of silicon dioxide added is slightly higher than that of palygorskite, the porosity of the resulting coating is less than 0.5%. It should be noted that the amount added is slightly higher than that of palygorskite, which means that the weight ratio of silicon dioxide to palygorskite is allowed to be in the range of (1.1-1.3):1.

[0021] Palygorskite, also known as attapulgite, has a chemical formula of (Mg,Al)2Si4O 10 (OH)·4H2O, has a special layered and channel structure, CAS number is 1337-76-4.

[0022] In the embodiment, the metal oxide with aluminum oxide as the base material also includes one or more of chromium oxide, iron oxide, zirconium dioxide, tantalum oxide, beryllium oxide, and titanium oxide. In one embodiment, the metal oxide includes aluminum oxide, chromium oxide, and iron oxide; in one embodiment, the metal oxide includes aluminum oxide, chromium oxide, iron oxide, and zirconium dioxide; in one embodiment, the metal oxide includes aluminum oxide, chromium oxide, iron oxide, zirconium dioxide, and tantalum oxide; in one embodiment, the metal oxide includes aluminum oxide, chromium oxide, iron oxide, zirconium dioxide, tantalum oxide, and beryllium oxide; in one embodiment, the metal oxide includes aluminum oxide, chromium oxide, iron oxide, zirconium dioxide, tantalum oxide, and beryllium oxide; in one embodiment, the metal oxide includes aluminum oxide, chromium oxide, iron oxide, zirconium dioxide, tantalum oxide, beryllium oxide, and titanium oxide; in one embodiment, the metal oxide includes aluminum oxide, chromium oxide, zirconium dioxide, tantalum oxide, beryllium oxide, and titanium oxide; in one embodiment, the metal oxide includes aluminum oxide, chromium oxide, iron oxide, zirconium dioxide, tantalum oxide, beryllium oxide, and titanium oxide.

[0023] In the implementation scheme, except for palygorskite and silica which should be added according to the content regulations, the other components are metal oxides based on alumina. When the metal oxide contains other oxides besides alumina, the addition amount of alumina in the total components is not less than 50wt%. For example, the coating includes 11.5wt% palygorskite, 12.65wt% silica, 50wt% alumina, 10wt% zirconium dioxide, 10wt% chromium oxide, and 5.85wt% tantalum oxide; for example, the coating includes 12wt% palygorskite, 14.4wt% silica, 55wt% alumina, 10wt% zirconium dioxide, 5wt% chromium oxide, and 3.6wt% iron oxide; for example, the coating includes 15wt% palygorskite, 16.5wt% silica, 52wt% alumina, 8.2wt% zirconium dioxide, and 8.3wt% tantalum oxide; for example, the coating includes 17.3wt% palygorskite, 22.49wt% silica, 58.1wt% alumina, and 2.11wt% zirconium dioxide.

[0024] In the present application, before the metal oxides, palygorskite and silicon dioxide are made into nano ceramic coatings, the metal oxides, palygorskite and silicon dioxide should be made into powders, wherein the size of silicon dioxide is 5-100nm, the D50 particle size is 20nm, and the sizes of palygorskite and metal oxide are both 5-10μm.

[0025] In the implementation scheme, the method of preparing the nano ceramic coating from metal oxide, palygorskite and silicon dioxide is: A uniform mixed powder of metal oxide, palygorskite and silicon dioxide is sprayed onto the surface of the substrate by flame spraying and cured at room temperature for a period of time; Then spray water on the coating surface and let it stand for a while; The coating is heat treated for a period of time.

[0026] In the implementation plan, the room temperature curing time after the mixed powder is sprayed onto the surface of the substrate should be no less than 1 hour and no more than 2 hours; the standing time after spraying water on the coating surface should be slightly shorter than the room temperature curing time, preferably 20 to 30 minutes; when the coating is heat treated, the coating should be kept in a temperature environment of 80 to 150°C for no less than 24 hours.

[0027] In the implementation scheme, when heat treating the coating, a heating furnace can be used to continuously heat the coating placed inside, or hot air can be used to heat the coating, that is, hot air is heated to 80~150℃ and then continuously blown to the coating.

[0028] In the implementation scheme, when the thickness of the coating is greater than 0.5 mm, the amount of water sprayed on the coating surface should be controlled at 3~5L / m 2 .

[0029] In the following description, each component in the mixed powder can be obtained from the market, so the source of each component is not described in detail. Example 1

[0030] The coating of this embodiment is prepared using 10 kg of mixed powder, which contains 15 wt% palygorskite, 16.5 wt% silicon dioxide, 55 wt% aluminum oxide, 5 wt% chromium oxide, 5 wt% zirconium dioxide, and 3.5 wt% tantalum oxide.

[0031] Preparation method 1 The mixed powder is made into a coating according to the following steps: The mixed powder was sprayed onto the substrate surface by flame spraying, with a coating thickness of 1 mm, and cured at room temperature for 1 hour. The substrate was 1Cr18Ni9Ti alloy steel plate. The flame spraying method used oxygen-acetylene fuel, and the acetylene pressure was 0.03 MPa. Then spray water on the coating surface and let it stand for 20 minutes. Spray water at 3L / m 2 The amount of spraying; Keep the coating in a hot air environment for 36 hours with a hot air temperature of 100±5℃.

[0032] Preparation method 2 The present invention provides an existing method for preparing nano ceramic coatings, wherein the mixed powder is prepared into coatings according to the following steps: The mixed powder is sprayed onto the surface of the substrate by the spray-melt method, the coating thickness is 1 mm, and it is cured at room temperature for 48 hours. The substrate is 1Cr18Ni9Ti alloy steel plate.

[0033] The mixed powder of Example 1 was used to prepare coating samples by Preparation Method 1 and Preparation Method 2, respectively. The coating sample prepared by Preparation Method 1 was marked as 1-1, and the coating sample prepared by Preparation Method 2 was marked as 1-2.

[0034] The porosity of the above samples was fitted and calculated using ImageJ software combined with the cross-sectional SEM morphology area of ​​the samples at the same magnification. The results are shown in Table 1.

[0035] Table 1 By comparing samples 1-1 and 1-2, it can be seen that when a coating is prepared with a mixed powder of metal oxides, palygorskite and silica as components, a coating with a porosity of less than 1% cannot be obtained by simply spraying the mixed powder onto the surface of the substrate using the conventional melt spraying method in the prior art. The difference is that after the coating is prepared by the melt spraying method in Preparation Example 1, the room temperature curing time is shortened, and after room temperature curing, the porosity of the coating is reduced to less than 1% by spraying water on the coating surface, allowing it to stand and heat treat it for a long time. Since palygorskite has adsorption properties, after the coating is made and cured at room temperature for a short time, the basic state of the coating can be maintained but it has not yet been completely solidified. After the water spray treatment, the palygorskite on the surface and inside of the coating absorbs water and expands, and combines with the surrounding silica, so that some nano-scale particles enter the micropores of the palygorskite, and some larger ions of about 20 nanometers are embedded in the mesoporous openings of the palygorskite, blocking the channels of the palygorskite and reducing the porosity of the palygorskite itself. At the same time, the combination of the palygorskite itself and the surrounding silica also improves the strength of the coating; after the palygorskite evenly distributed in the coating expands, it slightly squeezes the coating components that have not yet been completely solidified, increases the density of the components, and reduces the pores between the components; thereafter, by subjecting the coating to a long-term heat treatment, the coating structure is completely formed and its low porosity characteristics are maintained. Example 2

[0036] The coating of this embodiment is prepared by using 10 kg of mixed powder, and the mixed powder contains 15 wt % palygorskite, 16.5 wt % silicon dioxide, 55 wt % aluminum oxide, 5 wt % zirconium dioxide, and 8.5 wt % tantalum oxide. Example 3

[0037] The coating of this embodiment is prepared by using 10 kg of mixed powder, and the mixed powder contains 15 wt % palygorskite, 16.5 wt % silicon dioxide, 55 wt % aluminum oxide, 5 wt % chromium oxide, and 8.5 wt % tantalum oxide.

[0038] Comparative Example 1 The coating of this embodiment is prepared by using 10 kg of mixed powder, and the mixed powder contains 15 wt % palygorskite, 55 wt % aluminum oxide, 10 wt % chromium oxide, 10 wt % zirconium dioxide, and 10 wt % tantalum oxide.

[0039] Comparative Example 2 The coating of this embodiment is prepared by using 10 kg of mixed powder, and the mixed powder contains 16.5 wt % silicon dioxide, 55 wt % aluminum oxide, 10 wt % chromium oxide, 10 wt % zirconium dioxide, and 8.5 wt % tantalum oxide.

[0040] Using the mixed powders of Example 2, Example 3, Comparative Example 1, and Comparative Example 2, coating samples were prepared respectively by Preparation Method 1. The coating sample prepared in Example 2 was marked as 2-1, the coating sample prepared in Example 3 was marked as 2-2, the coating sample prepared in Comparative Example 1 was marked as 2-3, and the coating sample prepared in Comparative Example 2 was marked as 2-4.

[0041] The porosity of the above samples was fitted and calculated using ImageJ software combined with the cross-sectional SEM morphology area of ​​the samples at the same magnification. The results are shown in Table 2.

[0042] Table 2 By comparing samples 1-1, 2-3 and 2-4, it can be seen that the metal oxide as the coating base material has no significant effect on the porosity of the coating when its composition changes within a reasonable range; while by comparing samples 1-1, 2-1 and 2-2, it can be seen that the addition of palygorskite and silica has a relatively significant effect on the porosity of the coating, especially the porosity of the coating prepared by adding palygorskite and silica separately to the metal oxide has a slight decrease, but it is obviously not as good as the effect of adding palygorskite and silica at the same time.

[0043] Comparative Example 3 The coating of this embodiment is prepared by using 20 kg of mixed powder, which contains 15 wt% palygorskite, 12 wt% silicon dioxide, 55 wt% aluminum oxide, 10 wt% chromium oxide, 5 wt% zirconium dioxide, and 3 wt% tantalum oxide.

[0044] Comparative Example 4 The coating of this embodiment is prepared by using 20 kg of mixed powder, which contains 15 wt% palygorskite, 13.5 wt% silicon dioxide, 55 wt% aluminum oxide, 8 wt% chromium oxide, 5 wt% zirconium dioxide, and 3.5 wt% tantalum oxide.

[0045] Comparative Example 5 The coating of this embodiment is prepared by using 20 kg of mixed powder, which contains 15 wt% palygorskite, 15 wt% silicon dioxide, 55 wt% aluminum oxide, 7 wt% chromium oxide, 5 wt% zirconium dioxide, and 3 wt% tantalum oxide. Example 4

[0046] The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 15 wt % palygorskite, 18 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, 5 wt % zirconium dioxide, and 2 wt % tantalum oxide. Example 5

[0047] The coating of this embodiment is prepared by using 20 kg of mixed powder, which contains 15 wt % palygorskite, 19.5 wt % silicon dioxide, 50 wt % aluminum oxide, 8 wt % chromium oxide, 5 wt % zirconium dioxide, and 2.5 wt % tantalum oxide.

[0048] Comparative Example 6 The coating of this embodiment is prepared by using 20 kg of mixed powder, which contains 15 wt % palygorskite, 21 wt % silicon dioxide, 50 wt % aluminum oxide, 7 wt % chromium oxide, 5 wt % zirconium dioxide, and 2 wt % tantalum oxide.

[0049] Using the mixed powders of Example 4, Example 5 and Comparative Examples 3 to 6, coating samples were prepared respectively by Preparation Method 1, and the coating samples prepared from Comparative Example 3, Comparative Example 4, Comparative Example 5, Example 4, Example 5 and Comparative Example 6 were marked as 3-1 to 3-6.

[0050] The porosity of the above samples was fitted and calculated using ImageJ software combined with the cross-sectional SEM morphology of the samples at the same magnification. The bonding strength between the coating and the substrate was tested using a pull-off tester according to the standard "GB 5210-2006 Paint and varnish adhesion test by pull-off method". The results are shown in Table 3.

[0051] Table 3 By comparing samples 1-1, 3-1 to 3-6, it can be seen that with the increase of the amount of silica added in the total components, the porosity of the prepared coating has a more obvious trend of first decreasing and then increasing, and the porosity after sample 3-4 can reach below 1%, and the corresponding silica addition amount is 1.2 times that of palygorskite. However, as the amount of silica added continues to increase, the bonding strength between the coating and the substrate is also decreasing, especially in sample 3-6, the amount of silica added reaches 1.4 times that of palygorskite, and the bonding strength between the coating and the substrate drops below 50MPa. In many industrial application scenarios, the bonding strength between the coating and the substrate is required to be no less than 50MPa. Therefore, the most appropriate amount of silica added is between 1.1 and 1.4 times that of palygorskite.

[0052] Comparative Example 7 The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 8 wt % palygorskite, 8.8 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 23.2 wt % zirconium dioxide.

[0053] Comparative Example 8 The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 9 wt % palygorskite, 9.9 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 21.1 wt % zirconium dioxide.

[0054] Comparative Example 9 The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 10 wt % palygorskite, 11 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 19 wt % zirconium dioxide.

[0055] Comparative Example 10 The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 10.5 wt % palygorskite, 11.55 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 17.95 wt % zirconium dioxide.

[0056] Comparative Example 11 The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 11 wt % palygorskite, 12.1 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 16.9 wt % zirconium dioxide. Example 6

[0057] The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 11.5 wt % palygorskite, 12.65 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 15.85 wt % zirconium dioxide. Example 7

[0058] The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 12 wt % palygorskite, 13.2 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 14.8 wt % zirconium dioxide. Example 8

[0059] The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 13 wt % palygorskite, 14.3 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 12.7 wt % zirconium dioxide. Example 9

[0060] The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 14 wt % palygorskite, 15.4 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 10.6 wt % zirconium dioxide. Example 10

[0061] The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 15 wt % palygorskite, 16.5 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 8.5 wt % zirconium dioxide. Embodiment 11

[0062] The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 16 wt % palygorskite, 17.6 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 6.4 wt % zirconium dioxide. Example 12

[0063] The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 16.5 wt % palygorskite, 18.15 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 5.35 wt % zirconium dioxide. Embodiment 13

[0064] The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 17 wt % palygorskite, 18.7 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 4.3 wt % zirconium dioxide. Embodiment 14

[0065] The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 17.1 wt % palygorskite, 18.81 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 4.09 wt % zirconium dioxide. Embodiment 15

[0066] The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 17.2 wt % palygorskite, 18.92 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 3.88 wt % zirconium dioxide. Example 16

[0067] The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 17.3 wt % palygorskite, 19.03 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 3.67 wt % zirconium dioxide.

[0068] Comparative Example 12 The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 17.4 wt % palygorskite, 19.14 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 3.46 wt % zirconium dioxide.

[0069] Comparative Example 13 The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 17.5 wt % palygorskite, 19.25 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 3.25 wt % zirconium dioxide.

[0070] Comparative Example 14 The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 17.6 wt % palygorskite, 19.36 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 3.04 wt % zirconium dioxide.

[0071] Comparative Example 15 The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 18 wt % palygorskite, 19.8 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 2.2 wt % zirconium dioxide.

[0072] Comparative Example 16 The coating of this embodiment is prepared by using 20 kg of mixed powder, and the mixed powder contains 19 wt % palygorskite, 20.9 wt % silicon dioxide, 50 wt % aluminum oxide, 10 wt % chromium oxide, and 0.1 wt % zirconium dioxide.

[0073] Using the mixed powders of Examples 6 to 16 and Comparative Examples 7 to 16, coating samples were prepared respectively by Preparation Method 1, and the coating samples prepared from Comparative Examples 7 to 11, Examples 6 to 16 and Comparative Examples 12 to 16 were marked as 4-1 to 4-21.

[0074] The porosity of the above samples was fitted and calculated using ImageJ software combined with the cross-sectional SEM morphology of the samples at the same magnification. The bonding strength between the coating and the substrate was tested using a pull-off tester according to the standard "GB 5210-2006 Paint and varnish adhesion test by pull-off method". The results are shown in Table 4.

[0075] Table 4 By comparing samples 4-1 to 4-21, it can be seen that with the increase in the amount of palygorskite added in the total components, the porosity of the prepared coating has a more obvious trend of first decreasing and then increasing, and the porosity of samples 4-6 and later can reach below 1%, corresponding to an amount of palygorskite added of 11.5 wt%, and an amount of silica added of 1.1 times that of palygorskite. The porosity of samples 4-18 and later cannot reach below 1%, corresponding to an amount of palygorskite added of 17.5 wt%, and an amount of silica added of 1.1 times that of palygorskite. On the other hand, it can be seen that as the amount of palygorskite added continues to increase, the bonding strength between the coating and the substrate also decreases, and starting from sample 4-17, the bonding strength between the coating and the substrate drops below 50 MPa, and in the narrow range of palygorskite content of 17~18wt%, the inventors also conducted multiple verification tests, and the results all showed that when the amount of palygorskite added exceeds 17.3 After wt%, the bonding strength between the coating and the substrate can rarely reach 50MPa; therefore, the most appropriate amount of palygorskite added in the total components is 11.5~17.3 wt%.

[0076] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them.

Claims

1. A nano ceramic coating, characterized in that: The invention is composed of a metal oxide based on alumina, silicon dioxide and palygorskite, wherein the addition amount of the palygorskite is 11.5-17.3wt%, and the weight ratio of the silicon dioxide to the palygorskite is (1.1-1.3):1; The mixed powder of the metal oxide, silicon dioxide and palygorskite is flame-sprayed to form a coating, and then sprayed with water, left to stand and heat-treated to form a coating with a porosity of less than 1%.

2. A nano ceramic coating according to claim 1, characterized in that: The metal oxides also include one or more of chromium oxide, iron oxide, zirconium dioxide, tantalum oxide, beryllium oxide, and titanium oxide.

3. A nano ceramic coating according to claim 1, characterized in that: The addition amount of the aluminum oxide in the total components is not less than 50wt%.

4. A nano ceramic coating according to claim 1, characterized in that: The size of the silicon dioxide is 5-100 nm, and the D50 particle size is 20 nm.

5. The nano ceramic coating according to claim 1, characterized in that: After the coating is formed by flame spraying, it is cured at room temperature for 1 to 2 hours.

6. The nano ceramic coating according to claim 1, characterized in that: The standing time after spraying water is 20~30 minutes.

7. The nano ceramic coating according to claim 1, characterized in that: When the coating is heat treated, the temperature is 80~150℃ and the time is not less than 24h.

8. A method for preparing a nano ceramic coating, characterized in that: The preparation method is: Mixing the coating powder according to any one of claims 1 to 7 uniformly; The coating is sprayed on the surface of the substrate by flame spraying and cured at room temperature for 1~2h; Press 3~5L / m onto the coating surface 2 After spraying with water, let it stand for 20-30 minutes; The coating is heat treated at a temperature of 80~150℃ for not less than 24h.

9. An application of a nano ceramic coating, characterized in that: The coating according to any one of claims 1 to 7 is sprayed on the surface of the substrate to be protected to form a coating with a porosity of less than 1%, thereby blocking external corrosive components from contacting the substrate through the pores.